Effects of different acid treatments on dental ceramic surfaces - (:unkn) unknown (Trans Tech Publications Ltd, 2004)
In this study, effects of etching on a dental ceramic material were investigated. 9.6% hydrofluoric acid solution was used to etch 28 specimens which were prepared from the Finesse™ (trademark of Dentsply Inc.) core ceramic fabricated through ceramic hot pressing routes followed by ingot casting. The specimens were randomly divided into four groups. Three groups were etched at different times. The fourth group was the control group. 4-point bending tests and scanning electron microscopy (SEM) investigations were carried out on these specimens to determine the effects of etching on the flexural strength. Whereas the control group had better flexural strength values, there were no statistically significant differences between the strength values of the specimens of the three groups etched at different times.
Keywords: Acid treatment; Core ceramic; Flexural strength